Comparative performance of different lines of New Hampshire breed of poultry in Nepal (Nepal Agriculture Research Journal, 2023)
A study was conducted to evaluate the comparative performance of four different lines of New Hampshire (NH) poultry breed collected from different governmental farms of Pokhara, Parwanipur, Khajura and Khumaltar, Nepal. The study was undertaken for seven months from March to September 2020. The study included 160 chicks with 20 male and 20 female from each line. The experiment was conducted in a Completely Randomized Design with four treatments of different lines and eight replications. The results showed that the highest average weight of day-old chicks was found for Khumaltar line and the lowest for Pokhara line (p